Programming physical quantum systems with pulse-level control - Smith, Kaitlin N.; Ravi, Gokul Subramanian; Alexander, Thomas; Bronn, Nicholas T.; Carvalho, André R. R.; Cervera-Lierta, Alba; Chong, Frederic T.; Chow, Jerry M.; Cubeddu, Michael; Hashim, Akel; Jiang, Liang; Lanes, Olivia; et al. (Frontiers in Physics, 2022)
Quantum information processing holds great potential for pushing beyond the current frontiers in computing. Specifically, quantum computation promises to accelerate the solving of certain problems, and there are many opportunities for innovation based on proposed applications in chemistry, engineering, finance, and more. To harness the full power of quantum computing, however, we must not only place emphasis on manufacturing better qubits, advancing our algorithms, and developing quantum software. We must also refine device-level quantum control to scale to the fault tolerant quantum regime. On May 17-18, 2021, the Chicago Quantum Exchange (CQE) partnered with IBM Quantum and Super.tech to host the Pulse-level Quantum Control Workshop. At the workshop, representatives from academia, national labs, and industry addressed the importance of fine-tuning quantum processing at the physical layer. This work summarizes the key topics of the Pulse-level Quantum Control Workshop for the quantum community at large.